The correlation between cumulative cigarette consumption and infarction-related coronary spasm in patients with ST-segment elevation acute myocardial infarction across different age groups - Zhihui Kuang; Lin Lin; Ranran Kong; Zhonghua Wang; Xianjun Mao; Dingcheng Xiang (Scientific Reports)
Abstract Coronary artery spasm (CAS) is a key contributor to the pathogenesis of acute ST-segment elevation myocardial infarction (STEMI). While smoking is recognized as a major risk factor for CAS, the relationship between cumulative cigarette consumption and infarction-related CAS across different age groups in STEMI patients remains unclear. This study aimed to investigate the correlation between cumulative cigarette consumption and infarction-related CAS across different age groups through a retrospective analysis. This retrospective study included STEMI patients who underwent coronary angiography (CAG) at the General Hospital of Southern Theater Command, between December 2014 and March 2018. STEMI was diagnosed based on the 2017 European Society of Cardiology (ESC) guidelines. Patients were divided into CAS and non-CAS groups according to CAG results, and further categorized by age into three groups: young (≤ 45 years), middle-aged (46–59 years), and elderly (≥ 60 years). Cumulative cigarette consumption was calculated using the smoking index (cigarettes/day × years). Smoking status was graded as follows: grade 0 (non-smokers), grade 1 (index ≤ 100), grade 2 (index > 100 and ≤ 200), and grade 3 (index > 200). Statistical analyses, including Chi-square tests, Spearman correlation, and multivariate logistic regression were conducted to evaluate the relationship between smoking and CAS in different age groups. Among the 1156 STEMI patients analyzed, 80 (6.9%) were diagnosed with CAS. The CAS group exhibited a higher proportion of young adults (35.0% vs. 13.8%, P < 0.001) and grade 3 smokers (62.5% vs. 46.6%, P < 0.001) compared to the non-CAS group. A positive correlation between cumulative cigarette consumption and CAS was observed in all patients (r = 0.124, P < 0.001), heavy smoking (grade 2 and grade 3) was significantly associated with CAS in young adults (r = 0.321, P < 0.001) and middle-aged adults (r = 0.127, P = 0.006) but not in elderly patients. Logistic regression demonstrated that heavy smoking significantly increased CAS risk, with adjusted odds ratios of 6.397 for grade 2 smokers and 6.926 for grade 3 smokers, relative to non-smokers. Among heavy smokers( grade 2 and grade 3), young adults had a 4.912-fold higher CAS risk, while middle-aged adults had a 2.041-fold higher risk, compared to elderly individuals. Cumulative cigarette consumption is closely linked to infarction-related CAS in STEMI patients. Heavy smoking (grade 2 and grade 3) is a key factor linked to infarction-related coronary spasm, especially in younger and middle-aged adults. Effective smoking control is essential for preventing and managing STEMI, particularly among younger and middle-aged populations in China. Further validation of our findings using prospective studies and large registries is warranted.